Quality Assurance of Adverse Drug Reaction Reporting and Monitoring by Clinical Pharmacists in a Tertiary Care Teaching Hospital - Patel, Himanshu; Churi, Shobha; Gurumurthy, Parthasarathi; Madhan, Ramesh (Indian Journal of Pharmacy Practice)
Background: Patient care services provided by clinical pharmacists should be evaluated periodically to ensure the quality of service. Objectives: This study was conducted to evaluate impact of standard operating procedures (SOPs) on quality of adverse drug reaction (ADR) reporting. Methods: The study was conducted by department of clinical pharmacy located at tertiary care teaching hospital. Quality assessment checklist was designed to assess the quality of ADR reports received through spontaneous reporting system and continuous monitoring. Based on score obtained from checklist ADR reports were graded at different quality levels. Quality of ADR reports was compared before and after implementation of SOP. Results: Before implementation of SOP, total of 71 ADRs were evaluated, out of which 40.85% of them were found to be good, whereas 39.43% of ADRs could be improved. However, only 11.26% of ADRs were found to be excellent and 8.46% of them needed an attention to improve it. After implementation of SOPs, 61 ADRs were evaluated, out of which 67.21% of them were found to be excellent and 16.39% of them were found to be good. Conclusion: The quality of ADR reporting and monitoring was found to be improved after implementation of SOPs. Ongoing quality monitoring may further help in maintaining standards and efficiency of ADR monitoring program at the study hospital.
Keywords: Adverse drug reactions; Quality assurance; Standard operating procedures; Quality monitoring; Clinical Pharmacists